Pictorial Review of Surgical Anatomy in Adult Congenital Heart Disease. Issue 4 (July 2017) - De Cecco, Carlo N.; Muscogiuri, Giuseppe; Madrid Pérez, José M.; Eid, Marwen; Suranyi, Pal; Lesslie, Virginia W.; Bastarrika, Gorka
Abstract : The survival rate of patients with congenital heart disease (CHD) has dramatically improved over the last 2 decades because of technological and surgical advances in diagnosis and treatment, respectively. The vast majority of CHD patients are, in fact, amenable to treatment by either device closure or surgery. Considering the wide spectrum of surgical procedures and complex native and derived anatomy, continuous and detailed follow-up is of paramount importance. Cardiac magnetic resonance and cardiac computed tomography angiography are the cornerstones of diagnosis and follow-up of CHD, allowing for comprehensive noninvasive assessment of the heart, coronary tree, and intrathoracic great vessels, along with both morphological and functional evaluation. The aim of this pictorial review is to provide an overview of the most common CHDs and their related surgical procedures as familiarity with the radiological findings of grown-up congenital heart disease patients is crucial for proper diagnostic and follow-up pathways.